Comparison Of The Effectiveness Between Contrast Bath And Tens (Transcutaneous Electrical Nerve Stimulation) In Reducing Lactic Acid Levels Among Members Of The Binsik As.Sr Club - Muhammad al-hasani; Bazuri Fadilah Amin; Junaidi Junaidi; Nadya Dwi Oktafiranda (Universitas Negeri Jakarta, 2026)
This research was conducted with the primary objective of comparing the effectiveness of two recovery methods, namely Contrast Bath and Transcutaneous Electrical Nerve Stimulation (TENS), in reducing lactic acid levels among members of the Binsik AS.SR Club after engaging in intensive physical activity. The central problem addressed in this study is the accumulation of lactic acid, which is widely recognized as a major factor contributing to fatigue, muscle soreness, and decreased performance. Previous studies have generally examined only one of these methods in isolation, which limits the scope of understanding. To overcome this gap, the present study adopted a one-group pretest-posttest design, with lactic acid levels measured both before and after treatment. The sample consisted of athletes from the club who underwent recovery sessions using both Contrast Bath and TENS. Data collection was carried out through blood lactic acid testing with a portable device, and the results were analyzed using appropriate statistical tests. Findings revealed that Contrast Bath reduced lactic acid levels by an average of 1.8 mmol/L, while TENS achieved a greater reduction of 2.3 mmol/L. Both methods were statistically significant in accelerating recovery, yet TENS demonstrated superior effectiveness. The conclusion emphasizes that both strategies can be applied as practical post-training recovery approaches, offering valuable implications for coaches and athletes in selecting suitable rehabilitation techniques. This study is expected to serve as a useful reference for the advancement of sports science, particularly in the areas of muscle recovery and fatigue management.